The cobweb confession - Stanley, George Edward; Murdocca, Sal; Copyright Paperback Collection (Library of Congress) (New York : Aladdin Paperbacks, 2001)
Todd must conquer his fear of spiders and cobwebs in order to help his third-grade class catch a thief.
Keywords: Schools -- Fiction; Spiders -- Fiction; Spider webs -- Fiction; Mystery fiction; Fantasy fiction